Tinjauan Yuridis Terhadap Praktik Perjanjian Sewa Pacar Dalam Perspektif Kebebasan Berkontrak - Maulana Gibran, Ryan; Mara Ditta Caesar Purwanto, Aldira (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The advancement of digital technology has encouraged the emergence of new social practices in Indonesia, including the phenomenon of boyfriend rental services adapted from Japan (Rentaru Kareshi). This study analyzes the application of the principle of freedom of contract within such rental arrangements and assesses their validity based on Article 1320 of the Indonesian Civil Code. The research employs a normative juridical approach through statute and conceptual analyses, using data sourced from legislation, legal literature, academic journals, and other relevant materials. The findings show that boyfriend rental agreements are formed between users and service providers through digital platforms. Although Article 1338 of the Civil Code recognizes freedom of contract, this freedom is not absolute and remains limited by statutory provisions, propriety, and public order. Boyfriend rental agreements fail to meet the requirement of a lawful cause under Article 1320 because they contradict prevailing legal and religious norms in Indonesia. Romantic engagements have no firm legal basis and are considered inconsistent with religious values, particularly Islamic teachings that prohibit activities leading to immoral conduct.